Americanization of Non-American Storiesin Disney Films - Beta Setiawati (IAIN Salatiga, 2008)
The study is intended to know the Disney’s animation films characteristics which are adapted from non American stories that contain Americanization in order to be American popular culture products. This qualitative and library research is carried out within the field of American Studies. Disney’s animated films which are regarded as artifacts in order to identify American society and culture is used as her primary data. She then compares those Disney films with the original stories to discover the changes in making those stories become American popular products. She furthermore uses the sources such as books, magazines, journals, articles, and also internet data for her secondary data. The result of this study shows that most of folk narratives which were used in Disney films were adapted from other countries’ stories. However, Disney intentionally adapts foreign countries’ stories in its animated films by using Disney formula to blow up the sale of its products. Since Disney is one of the most powerful media conglomerates in the world, it works endlessly to set out world entertainment. Disney formula in its animated films which has dominated those adapted films are only intended to obtain as much profit as possible without paying attention to the values in children entertainment.Keywords: Americanization; Non American Stories; Animation; Popular culture; Formula